P09.25 Duration of syphilis symptoms at presentations in men who have sex with men in australia: are current public health campaigns effective?. (13th September 2015) - Chow, EPF; Dutt, K; Fehler, G; Denham, I; Chen, MY; Batrouney, C; Peel, J; Read, TRH; Bradshaw, CS; Fairley, CK
Abstract : Introduction: The rapid rise in syphilis has prompted a number of public health campaigns to assist men who have sex with (MSM) men recognise and present early with symptoms. This study aimed to investigate the temporal trend of the duration of self-report symptoms and titre of rapid plasma regain (RPR) among MSM with infectious syphilis in relation to these campaigns. Methods: 761 syphilis cases among MSM diagnosed at the Melbourne Sexual Health Centre (MSHC) from 2007–2013 were reviewed. Median and interquartile range (IQR) of duration of symptoms and RPR titres in each year were calculated. Results: The median duration of symptoms for MSM with primary and secondary syphilis were 9 days (IQR: 6–14) and 14 days (IQR: 7–30), respectively. The overall median titre of RPR in secondary syphilis (128; IQR: 64–256) was higher than in primary (4; IQR: 1–32) and early latent syphilis (32; IQR: 4–64). The median duration of symptoms for primary (p = 0.11), secondary (p = 0.24) and titre of RPR level for primary (p = 0.35), secondary (p = 0.08), and early latent syphilis (p = 0.85) did not change over time. A strong positive correlation was observed between duration of symptoms and RPR titre in both primary (r = 0.36, p < 0.001) and secondary (r = 0.16, p = 0.05) syphilis. Conclusion: Public health campaigns were not associated with a significant shorter time from onset of symptoms to treatment. Either more effective campaigns or alternative strategies such as more frequent testing in MSM should be promoted to control the syphilis epidemic in Australia. Disclosure of interest statement: None.